PENGARUH ATRIBUT PRODUK DAN LABEL HALAL SEBAGAI VARIABEL MPDERATING TERHADAP KEPUTUSAN PEMBELIAN PRODUK KEMASAN DI KOTA MEDAN - Yossie Rossanty (JUMANT, 2016)
This study aims to determine the effect of product attributes and halal label asmoderating variables on product purchasing decisions packaging in KotaMedan.Populasi in this study is consumers who buy packaged products which havea halal label in the city of Medan were countless, so the population is not knownsurely. Samples were obtained from some consumers who have already purchasedthe product packaging has a halal label in the city of Medan. The samplingtechnique used by non-probability sampling. The sample size is of 110 respondents.The data used is primary data collection method of data using questionnaires. Theanalysis technique used is multiple regression with moderating variablesTarget specialized in the research is very important to do, considering the majorityof residents in the city of Medan 67.8% are Muslims, it is unfortunate if it can notconsume halal sharia-compliant products. Expected outcomes of this research is tobe published in scientific journals that have become ISSN and additionalinformation in making teaching materials on the subject Marketing Management.This study will be conducted in 21 districts in the city of Medan. Old study isscheduled for 6 months.